Physiology governing diatom vs. dinoflagellate bloom and decline in coastal Santa Monica Bay - Ollison, Gerid A.; Hu, Sarah K.; Hopper, Julie V.; Stewart, Brittany P.; Beatty, Jennifer L.; Caron, David A. (Frontiers in Microbiology, 2023)
Algal blooms on the Southern California coast are typically dominated by diatom and dinoflagellate taxa, and are governed by their physiological responses to environmental cues; however, we lack a predictive understanding of the environmental controls underlying the establishment and persistence of these distinct bloom events. In this study, we examined gene expression among the numerically dominant diatom and dinoflagellate taxa during spring upwelling bloom events to compare the physiological underpinnings of diatom vs. dinoflagellate bloom dynamics. Diatoms, which bloomed following upwelling events, expressed genes related to dissolved inorganic nitrogen utilization, and genes related to the catabolism of chitin that may have prolonged their bloom duration following nitrogen depletion. Conversely, dinoflagellates bloomed under depleted inorganic nitrogen conditions, exhibited less variation in transcriptional activity, and expressed few genes associated with dissolved inorganic nutrients during their bloom. Dinoflagellate profiles exhibited evidence of proteolysis and heterotrophy that may have enabled them to bloom to high abundances under depleted inorganic nutrients. Taken together, diatom and dinoflagellate transcriptional profiles illustrated guild-specific physiologies that are tuned to respond to and thrive under distinct environmental “windows of opportunity.”